2013
DOI: 10.1038/leu.2013.91
|View full text |Cite
|
Sign up to set email alerts
|

Global H3K4me3 genome mapping reveals alterations of innate immunity signaling and overexpression of JMJD3 in human myelodysplastic syndrome CD34+ cells

Abstract: The molecular bases of myelodysplastic syndromes (MDS) are not fully understood. Trimethylated histone 4 lysine 3 (H3K4me3) is present in promoters of actively transcribed genes and has been shown to be involved in hematopoietic differentiation. We performed a genome-wide H3K4me3 CHIP-Seq analysis of primary MDS bone marrow (BM) CD34+ cells. This resulted in the identification of 36 genes marked by distinct higher levels of promoter H3K4me3 in MDS. A majority of these genes are involved in NF-kB activation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 61 publications
7
87
0
Order By: Relevance
“…Similarly, previous work of a large-scale reverse genetic screen found that knockdown of jmjd3 promotes mature erythrocyte markers β-E3 expression at 17 hpf [55]. Consistently, Peripheral blood CD34+ progenitor cells in patients with lower-risk MDS (myelodysplastic syndromes) have increased expression of JMJD3 and an increased ability to form erythroid colonies upon inhibition of JMJD3 [56]. This suggests that Jmjd3 is intimately involved in erythroid lineage determination.…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, previous work of a large-scale reverse genetic screen found that knockdown of jmjd3 promotes mature erythrocyte markers β-E3 expression at 17 hpf [55]. Consistently, Peripheral blood CD34+ progenitor cells in patients with lower-risk MDS (myelodysplastic syndromes) have increased expression of JMJD3 and an increased ability to form erythroid colonies upon inhibition of JMJD3 [56]. This suggests that Jmjd3 is intimately involved in erythroid lineage determination.…”
Section: Discussionsupporting
confidence: 58%
“…Consistent with the hypothesis that reduced A20 expression and increased innate immune function is associated with MDS 144 , empirical data revealed A20 mRNA is significantly reduced in CD34+ cells isolated from the BM of MDS patients 145 . Moreover, miR-125a, which targets A20, is overexpressed in MDS CD34+ cells 16,146 .…”
Section: Negative Regulators Of Innate Immune Signaling In Mdssupporting
confidence: 62%
“…We recently performed a genome-wide CHIP-Seq analysis of H3K4me3 in MDS. 2 This analysis identified multiple genes marked by increased H3K4me3 in BM CD34+ cells. A large majority of the genes identified are known to be involved in Toll-like receptor (TLR) mediated innate immunity signaling and NF-kB activation.…”
Section: Introductionmentioning
confidence: 96%